Chitosan nanoparticles loaded hydrogels promote skin wound healing through the modulation of reactive oxygen species. (31st October 2018) - Wang, Tao; Zheng, Yan; Shen, Yaping; Shi, Yijie; Li, Fang; Su, Chang; Zhao, Liang
Abstract: This study developed a novel bioactive chitosan nanoparticle loaded calcium alginate hydrogel to regulate inflammation and neovascularization for accelerated wound healing in vivo . It was found that chitosan nanoparticles loaded calcium alginate hydrogel exhibited remarkable antibacterial activity. Through the modulation of generation of ROS, it promoted the synthesis and secretion of IL-6 in vascular endothelial cell (VEC), suggesting its potential proinflammatory activation. Further, it promoted VEC invasion, metastasis and neovascularization to accelerate wound healing.